Character Building dan Anti-corruption Education: Mampukah Menciptakan Branding, Perilaku Anti Koruptif dan Good Personality Calon Akuntan Berintegritas? - Suryani, Pesi; Ginting, Rafles; Gaol, Lasando Lumban (Prodi Akuntansi FEBM Universitas Maritim Raja Ali Haji, 2025)
This study aims to examine the role of character-building values and anti-corruption education in creating branding, anti-corruptive behavior, and integrity in prospective accountants. The research employs a qualitative method with a phenomenological approach to explore the experiences and perceptions of accounting lecturers and students. Data were collected through in-depth interviews, observations, and document analysis, including lesson plans (RPS), syllabi, assignments, and evaluations. The findings indicate that character building and anti-corruption values have been implemented in learning through various components, including lesson plans, syllabi, assignments, and evaluations. The program significantly enhances the branding of prospective accountants in the job market, fosters consistent anti-corruptive behavior, and develops strong personal integrity. However, challenges remain, such as the lack of integration of these values into the formal curriculum and limited training for lecturers. The implications of this study highlight the importance of integrating character building and anti-corruption values into all aspects of the accounting education curriculum. Continuous training for lecturers and students is also necessary to ensure the sustainability of these values.